Study on GFP-labeling and mycoparasitism in Chaetomium globosum - YE Li-dan; LAO Jia-ping; LU Jian-ping; LIN Fu-cheng (浙江大学学报. 农业与生命科学版, 2007)
As an important biocontrol agent, the antagonistic mechanism of Chaetomium globosum to phytopathogens still leaves a lot to be studied. This paper aimed to investigate the antagonism between Chaetomium globosum and Rhizoctonia solani with GFP (green fluorescent protein) as reporter gene. Sulfonylrate -resistant transformants were obtained by construction and transformation of EGFP(Enhanced GFP)-expression vectors. After rounds of verification, including screening with selective plates, PCR amplification of targeted fragment, Southern blot and examination under fluoroscope, SUR and EGFP fragments were proved to be inserted and expressed in the genome of C. globosum. One fluorescing transformant was chosen to do biocontrol analysis. The mechanism of antagonism between C. globosum and R. solani was studied in the way of co-culture on plate and confrontation on slide. It is found that C. globosum has apparent process of mycoparasitism during the confrontation with R. solani.